Utilization of virgin coconut oil as an effort for promotion and prevention of diabetic foot in PROLANIS participants - Ismail, Dina Dewi Sartika Lestari; Adi, Setyo; Kristianingrun, Niko Dima; Dwi, Arisma Septia; Nurdiana, Sevia; Astuti, Fitri Dwi; Davelin, Valencia Nadya Carissa (Caring: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to improve participants' knowledge and skills in diabetic foot care through foot exercise and massage training using Virgin Coconut Oil (VCO). A total of 80 participants took part in the intervention, which included counseling, demonstrations, and questionnaire completion. The evaluation results showed a significant increase in participants' knowledge, with a decrease in the number of participants in the low category from 50% to 12.5% and an increase in the high category from 12.5% to 37.5%. An improvement in skills was also observed, where foot exercise skills increased from 18.8% to 43.8%, while foot massage skills rose from 12.5% to 56.2% after the intervention. Interactive education improves knowledge and skills; regular programs with healthcare professionals and social media use are recommended to promote diabetic foot care.